2007
DOI: 10.1038/sj.onc.1210822
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of nm23-H1 by CKI induces its complex formation with h-prune and promotes cell motility

Abstract: The combination of an increase in the cAMP-phosphodiesterase activity of h-prune and its interaction with nm23-H1 have been shown to be key steps in the induction of cellular motility in breast cancer cells. Here we present the molecular mechanisms of this interaction. The region of the nm23-h-prune interaction lies between S120 and S125 of nm23, where missense mutants show impaired binding; this region has been highly conserved throughout evolution, and can undergo serine phosphorylation by casein kinase I. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 45 publications
3
51
0
Order By: Relevance
“…These domains are followed by a cortexillin-homology domain (CHD, 370-453 residues) containing putative coiled-coil and proline-rich regions. The C-terminal region of h-prune is responsible for the h-prune interaction with GSK-3b (330-453 residues) and NM23-H1 in the phosphorilated form (393-453 residues), as described in [22]. The C-terminal region between 393 and 420 residues is essential for this dimerization.…”
Section: H-prune and Nm23-h1 In Cancermentioning
confidence: 96%
See 1 more Smart Citation
“…These domains are followed by a cortexillin-homology domain (CHD, 370-453 residues) containing putative coiled-coil and proline-rich regions. The C-terminal region of h-prune is responsible for the h-prune interaction with GSK-3b (330-453 residues) and NM23-H1 in the phosphorilated form (393-453 residues), as described in [22]. The C-terminal region between 393 and 420 residues is essential for this dimerization.…”
Section: H-prune and Nm23-h1 In Cancermentioning
confidence: 96%
“…Moreover, using pull-down and mass-spectrometry analyses, we have shown that h-prune binding to gelsolin, an ATP-severing protein that acts in focal adhesions, leads to invasive properties for cancer cells [22]. Gelsolin is involved in cytoskeleton remodelling, thus promoting cell motility.…”
Section: H-prune and Its Protein Partnersmentioning
confidence: 98%
“…Prune was initially reported to bind Nm23-H1 using interaction mating assays, in which the P96S (killer of prune) mutation of Nm23 continued to interact, but the S120G mutant protein was impaired (Reymond et al 1999). Co-immunoprecipitation of Prune and Nm23-H1 was demonstrated in MDA-MB-435 breast carcinoma cells (Garzia et al 2008). In biochemical and functional assays, Nm23-H1 and Prune also appear to interact: the PDE activity of Prune was enhanced by the presence of Nm23-H1.…”
Section: Other Pathwaysmentioning
confidence: 97%
“…A mechanistic understanding of NDPK/ Nm23/Awd-Pn interaction was resolved in mammalian cells when a direct interaction was revealed by two-way co-immunoprecipitation assays using endogenous levels of protein expression (Reymond et al 1999). Further refinement of this interaction identified the region on NDPK/ Nm23/Awd responsible for the interaction, serines 120, 122, and 125 (Garzia et al 2008). These mutations, alone or in combination, impaired the formation of NDPK/ Nm23/Awd-Prune complex.…”
Section: Concernsmentioning
confidence: 99%
“…These mutations, alone or in combination, impaired the formation of NDPK/ Nm23/Awd-Prune complex. NDPK-A/Nm23-H1 S120 is highly conserved throughout evolution and undergoes serine phosphorylation by casein kinase I (CKI), which is essential for the formation of the NDPK-A/Nm23-H1-Pn complex (Garzia et al 2008). As reported in this issue of Naunyn-Schmiedeberg's Archives of Pharmacology, a naturally occurring mutant of NDPK-A at S120, the S120G mutant, has the tendency to aggregate into amyloid structures (Georgescauld et al 2011).…”
Section: Concernsmentioning
confidence: 99%